PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTIONS AND GETTING ANSWER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 SUTERA KABUPATEN PESISISR SELATAN - Oktarani, Fevi; Husna, Husna; Zulfaneti, Zulfaneti (Pendidikan Matematika, 2014)
ABSTRACT This research is caused students low understanding of mathematical concepts and difficult to express ideas . This study aims to determine whether students understanding of mathematical concepts by applying Active Learning Strategies Type Giving Questions And Getting Answers a better understanding of the mathematical concepts that students applying conventional learning on eighth grade students of SMP Negeri 4 SUTERA . This type of research is experimental research . The population in this study is the class of eighth grade students of SMP Negeri 4 SUTERA . Technique of random sampling , the class is a class VIII.4 chosen as the experimental class and the control class as a class VIII.2 . The instrument used is a comprehension test with indicator concepts . Form of the test used is an essay , test questions totaling 13 items with a reliability of 0.88 . The test results were analyzed with the understanding of the concept of student t test , obtained = 5.02 and  for = 1.64 because  <  the hypothesis is accepted at the 95% confidence level . So it is concluded that the students understanding of mathematical concepts by applying Active Learning Strategies Type Giving Questions And Getting Answers a better understanding of the mathematical concepts that students applying conventional learning on eighth grade students of SMP Negeri 4 SUTERA .